Knowledge, Attitude and Practice of Community Health Workers Regarding Child Abuse in Tabriz Health Centers in 2015-2016 - Sahebihagh, Mohammad Hasan (Int J Community Based Nurs Midwifery, 2017)
BACKGROUND: Child abuse is a widespread social phenomenon with serious life-time consequences. Since parents bring their children to healthcare centers for growth screening and vaccinations, Community Health Workers play an important role in identifying and reporting child abuse cases. Thus, the current study aimed to investigate knowledge, attitude and performance of Community Health Workers regarding child abuse in Tabriz. METHODS: This is a descriptive (cross-sectional) study; census method was used for sampling. Study population consists of 265 people, employed at units of family health and vaccination in Tabriz healthcare centers in 2015-2016. A questionnaire was used to collect the data. Data analysis was carried out using SPSS, version 23 through descriptive (mean and standard deviation) and analytical (Two Independent Samples T-test and analysis of variance) statistics. RESULTS: Findings indicate that 58.5 percent of Community Health Workers had good knowledge about causes of child abuse and 45 percent had good knowledge of the signs, symptoms and complications of child abuse. Their total knowledge was good (57%). The mean score of awareness (knowledge) was significant according to the variable of training participation (P=0.04). The participants had a favorable attitude toward dealing with child abuse (91.3 %); the mean score of attitude was significant according to the educational field (P<0.001) and their performance in dealing with child abuse was moderate and lower (94.3 %). CONCLUSION: Community Health Workers had good knowledge regarding child abuse, favorable attitude toward dealing with child abuse, and poor performance in dealing with child abuse. This may be due to fear of side issues to deal with child abuse, or lack of clear legal guidelines regarding this.